Design of IoT Based Indoor Planting Media Quality Monitoring System - Zakaria, Alief Zakaria; Waluyo, Waluyo; Dali, Sri Wahyuni; Suprianto, Dodit (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Indoor plants have become a popular choice for many people in urban environments with limited space for gardening. However, proper care of indoor plants often requires careful monitoring and control of environmental factors such as temperature, humidity, lighting, and watering. In an effort to address these challenges, this study aims to design and build an Internet of Things (IoT)-based indoor plant control system using the Telegram application as the user interface. The system is designed to automatically monitor and control the environmental conditions around indoor plants. IoT sensors connected to the system hardware measure these environmental parameters and send the data to a server. Users can then access and control the system through the Telegram application on their mobile devices or computers. The system also notifies users if there are changes in conditions that require action. The results of this study include the development of an efficient IoT control system, a customized Telegram application, and complete technical documentation. The study identifies security and privacy issues related to the use of the Telegram application in this context and proposes appropriate solutions. Overall, this system combines IoT technology with popular applications to provide practical benefits to indoor plant owners with a remote plant monitoring and care system that can make their work easier. system shows its effectiveness in optimizing indoor plant growth and improving the quality of life with healthy and fertile plants.